Cross- and trans-language morphology; The lexicography of Indonesian names - van der Meij, Dick (UI Scholars Hub, 2010)
Different form many other name-giving possibilities in the world, in Indonesia parents are free to give their children any name they like. These names, many of which are auspicious in view of the child's future, are often constructed by means of productive morphological procedures. Seven suffixes are followed through history and culture and their possibilities in making new names are explored. The suffixes concern the female -ingsih, -ingrum, -ingtyas, -ingdyah, -astuti, -wati, and the male -wan. Various ins and outs concerning these suffixes are explored and their attachments to various words from various word classes from Indonesian, Javanese and other language revealed. Cross-language name construction leads to trans-language creations that play a possible role in the constitution of Indonesian nation building. The procedures moreover seem to indicate trends away from the inclination to give children Muslim names.